ISLAM NUSANTARA; SOCIAL ENGINEERING DA'WAH PERSPECTIVE WALI SONGO - Totok Agus Suryanto (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2022)
ABSTRACT This research aims to describe the social engineering of da'wah practised by Wali Songo and the scholars afterwards. The research approach used is qualitative with a descriptive type of literature study. This is important to do considering that until now the process of da'wah by bringing together religion and culture in the social system of Wali Songo remains a beautiful trend in introducing religious values in the community. It is not uncommon for the familiar encounter of religion and culture in the realm of da'wah to give birth to a unique expression that later became known as Islam Nusantara. Islam Nusantara in a very broad sense can be interpreted as a fermentation of religion and culture that institutionalizes in the format of religious social reality and becomes a characteristic made in the original archipelago which is nothing but a product of social engineering of the scholars of the archipelago itself. Keywords: Islam Nusantara, Social Engineering, Wali Songo Da'wah.